Biogeochemical processes in forest riparian zones - Ledesma, José L. J. (2016)
The area of interaction between terrestrial and aquatic environments, i.e. the riparian zone (RZ), has long been recognized as an important landscape feature from both scientific and management perspectives. Surface water quality is to a great extent regulated by substances exported from RZs. Boreal forest RZs are characterized by high organic matter content, which drives important biogeochemical processes. The overall objective of this thesis was to develop the understanding of RZ biogeochemical processes so as to provide a sound scientific basis for protection of surface water quality in boreal forests. The work was based on measurements from stream, riparian, and upslope monitoring sites in the 68 km² Krycklan catchment in northern Sweden. Specifically, the study of dissolved organic carbon (DOC), base cations (BC), silicon (Si), and sulfate (SO₄²⁻) was included. Opposite SO₄²⁻ and DOC trends were observed in both stream and riparian water, whereas no trends were apparent in the upslope area. This suggests that RZ processes control stream SO₄²⁻ and DOC independently of upslope soils. On the other hand, the upslope signal of BC and Si was maintained through the RZ and subsequently exported to the streams. RZs were found to have a long-term potential to export DOC from both new and old carbon pools. This, in combination with predicted future climate and exhaustion of residual S pools accumulated during the acidification period, is likely to increase DOC concentrations affecting surface water quality and the global carbon cycle. The hydrological connectivity between RZs and streams can be conceptualized as a ‘dominant source layer’, the narrow depth range with the highest contribution to solute and water fluxes. Local hydromorphology drives spatial heterogeneity in the distribution of RZs and in the intensity of their biogeochemical functions including retention via interaction with organic matter and transformation via redox reactions. Overall, this thesis provides new insights into the role of the RZ in ...